Design and Manufacture Ballast Management System Model for Reduce Ship Rolling Motion - Yulianto, Totok; Hermawan, Yuda Apri; Widjaja, Raden Sjarief; Purwanto, Dedi Budi; Sulaiman, Suardi bin; Rahmi, Lista Putri Adinda (Department of Naval Architecture - Diponegoro University, 2023)
The safety of maritime transportation is a critical aspect that must be addressed to ensure the well-being of ships and their crew. Frequent ship accidents highlight the need for improvements in the maritime transportation system. One of the causes of ship accidents is ship instability, leading to a loss of balance and even sinking. Ship stability is influenced by both internal and external factors, including human negligence in observing and addressing ship instability. This research aims to design and create a management ballast system model that can be operated automatically as a solution to reduce ship rolling motion. This system enables the ship to maintain balance using automatic side ballast tank management by utilizing two wing tanks on either side of the ship. The ballast management system will be equipped with an accurate ship roll angle detector, the Initial Measurement Unit sensor, a microcontroller, and a series of actuators, including relays as voltage control switches for the pump motor. This research involves simulation and testing/experiments at various angles, namely 5, 10, and 15 degrees. Simulations are conducted under conditions with and without the ballast management system, which is then confirmed through experiments under the same conditions. The expected outcome of this research is that the created ballast management system can be used to reduce ship rolling.